33.6k views
4 votes
Last one pleaseeeeeee

Last one pleaseeeeeee-example-1
User Mrwweb
by
5.2k points

2 Answers

4 votes
The answer is 7 hope this helps :)
User Swordsman
by
6.2k points
3 votes

Answer:


C) 7

Explanation:


Let\ p(x)\ be\ x^3+kx^2+7x+5\\Let\ g(x)\ be\ (x+6).\\Hence, \ \\The\ zero\ of\ g(x) :\\(x+6)=0\\x=-6\\\\Hence,\\p(x)\ =\ x^3+kx^2+7x+5\\p(-6)=(-6)^3+k(-6)^2+7*-6+5\\=-216+36k-42+5\\=-253+36k\\\\Through\ Remainder\ Theorem\ we\ get\ that\ R=-1\ &\ R=-253+36k [Given]\\Hence,\\-253+36k=-1\\36k=-1+253\\36k=252\\k=7

User SomethingSomething
by
5.3k points